A mechanistic study of SCC in Alloy 600 through high-resolution characterization. (March 2018) - Shen, Zhao; Arioka, Koji; Lozano-Perez, Sergio
Highlights: The effect of grain boundary type on crack growth rate was investigated by high-resolution characterization. Several necessary precursors to SCC were identified. The dominant mechanism controlling SCC was internal oxidation. A new understanding of the internal oxidation-induced SCC propagation was developed. Abstract: High-resolution characterization was used to understand the mechanisms controlling stress corrosion cracking (SCC) in Alloy 600 exposed to simulated PWR primary water conditions. Three potential active crack tips obtained from different types of grain boundaries were studied and compared. The results suggest that the dominant mechanism controlling SCC propagation is intergranular internal oxidation. The applied stress, pre-existent residual strain, the accumulation of defects around the crack tip, the formation of a Fe-Cr-depleted zone, and a porous intergranular oxide are acknowledged as necessary precursors to SCC. Based on the results obtained in this study, a model of SCC propagation is proposed.